HIGH-FREQUENCY MICROINDUCTOR ON THE BASE OF FLEXIBLE POLYIMIDE FILM - A. V. Petrov; S. E. Demyanov; E. Yu. Kaniukov; D. Fink (Приборы и методы измерений)
A method of creation of 3D flexible high-frequency microinductor on the base of polyimide film with etched swift heavy ion tracks, filled with a conducting material is proposed. This methos is more simple as compared with existing technologies. The service model of the microinductor having dimensions 0,04 mm3 is fabricated. This model has following main operational characteristics: winding density of 7 winding/mm at the winding thickness 10 μm; inductivity 0.3 mH with the Q-factor of 8 at 200 MHz. A possibility of the decrease of dimensions of the device down to 10-6 mm3 is shown.